Cardiac Disease in Limb-girdle Muscular Dystrophy Type 2 (Nigerian Journal of Health Sciences, 2023)
Limb‑girdle muscular dystrophy is a rare inheritable muscle disease, and cardiovascular involvement is of prognostic significance. Only a few cases have been reported in our population. We, therefore, present the case of a 20‑year‑old student who was referred to the cardiac clinic on account of cardiomegaly on routine chest X‑ray. He had dyspnoea on exertion, and occasional palpitations. There was a history of difficulty with standing from a sitting position, climbing stairs and raising his upper limbs above his head. His younger sister also has difficulties performing these tasks but has no cardiac symptoms. On examination, there was bilateral proximal muscle weakness with severe atrophy and an abnormal gait. There was sinus bradycardia on electrocardiography. Echocardiography revealed dilated cardiac chambers with ventricular dysfunction.